Subassemblage tests and analysis of buckling-restrained braced reinforced concrete frames with various gusset connections. (May 2022) - Wang, Jingfeng; Lu, Fei; Li, Beibei
Abstract: The buckling-restrained brace (BRB) is an effective energy dissipation damper, which can effectively improve the lateral stiffness, strength and energy dissipation capacity of reinforcement concrete (RC) structures. However, few studies have been conducted on the influences of gusset plate connection type on BRB rotations and seismic performance of braced RC frames. In this study, subassemblage quasi-static cyclic test was performed to five buckling-restrained braced RC frame subassemblages (BRBRCFs) with various gusset plate connections, including bolted gusset plate connection, welded gusset plate connection, pinned gusset plate connection, bolted-pinned gusset plate connection and welded-pinned gusset plate connection. The effects of various gusset connections on failure modes, ductility, stiffness degradation, energy dissipation capacity, gusset plate and BRB end zone rotation deformations of the subassemblages were evaluated and discussed. The test results indicated all specimens exhibited stable hysteretic behavior and excellent ductility with negligible degradation of stiffness and strength at the same loading level. The rotation responses of the gusset plate were generally greater than those of BRB end zone. Additionally, the finite element (FE) model of BRBRCFs with various gusset plate connections was established and verified using experimental results. This study facilitates applications of BRBs with various gusset plate connections in RC frame structures.